Artificial intelligence and big data in the Maritime Silk Road Initiative: The road towards Sea Power 2.0 - Hlongwa, Lungani Nelson (Scientia Militaria - South African Journal of Military Studies, 2021)
China’s Belt and Road Initiative continues to attract considerable attention from scholars and observers in diverse fields. However, students of the Belt and Road Initiative (‘the Initiative’) have focused extensively on the land and sea dimensions of this grand project while only tentatively touching on its other dimensions. This article draws attention to the digital and maritime dimensions of the Initiative, which are respectively known as the Digital Silk Road Initiative and the Maritime Silk Road Initiative. Specifically, the article focuses on how artificial intelligence and big data, as promoted under the Digital Silk Road Initiative, intersect with the Maritime Silk Road Initiative to produce what the author refers to as Sea power 2.0. To contextualise this intersection, the article draws on patent data to show how artificial intelligence and big data are adopted in supply chains. The results from the patent analysis show that artificial intelligence and big data will play a crucial role in future supply chains, and hence, the Maritime Silk Road Initiative. Although the article focuses mostly on the commercial side of Sea power 2.0, it concludes by pointing out how artificial intelligence and big data could serve military objectives.